2016
DOI: 10.17219/acem/37451
|View full text |Cite
|
Sign up to set email alerts
|

Impacted Teeth: An Interdisciplinary Perspective

Abstract: A tooth normally erupts when half to three-quarters of its final root length has developed. Tooth impaction is usually diagnosed well after this period and is generally asymptomatic. It is principally for this reason that patients seek treatment later than optimal. Tooth impaction is a common problem in daily orthodontic practice and, in most cases, it is recognized by chance in a routine dental examination. Therefore, it is very important that dental practitioners are aware of this condition, since early dete… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
53
0
16

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 65 publications
(70 citation statements)
references
References 23 publications
1
53
0
16
Order By: Relevance
“…Treatment plan depends on several factors, primarily on the ammount of space available to initiate the emergance of impacted tooth, depth of impaction, degree of root formation, need for first molar extraction, duration of the therapy and presence of keratinized gingiva. In addition, treatment plan is significantly influenced by the patient`s state of general health, other teeth and oral hygiene, as well as function and occlusion [9,10]. Andreasen recommended surgical exposure of impacted premolar to be limited to cases where the angulation of the tooth is not greater than 45° in both jaws.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Treatment plan depends on several factors, primarily on the ammount of space available to initiate the emergance of impacted tooth, depth of impaction, degree of root formation, need for first molar extraction, duration of the therapy and presence of keratinized gingiva. In addition, treatment plan is significantly influenced by the patient`s state of general health, other teeth and oral hygiene, as well as function and occlusion [9,10]. Andreasen recommended surgical exposure of impacted premolar to be limited to cases where the angulation of the tooth is not greater than 45° in both jaws.…”
Section: Discussionmentioning
confidence: 99%
“…Kakav način terapije će biti odabran zavisi od više faktora, pre svega od postojanja dovoljno prostora za nicanje impaktiranog zuba, dubine impakcije, stepena formiranosti korena, potrebe za ekstrakcijom prvog molara, dužine trajanja terapije, prisustva keratinizovane gingive. Osim njih, značajan uticaj imaju i opšte zdravstveno stanje pacijenta, stanje zuba i oralne higijene, kao i funkcija i okluzija zuba [9,10]. Andreasen [1] preporučuje da hirurško eksponiranje impaktiranih premolara treba biti ograničeno samo na slučajeve kada angulacija zuba nije veća od 45° i u gornjoj i donjoj vilici.…”
Section: Diskusijaunclassified
“…This situation is frequently associated to permanent tooth as wisdom teeth and canines. [2][3][4] Moreover, primary tooth impaction is a rare condition during the development of primary dentition [5]. The presence of primary tooth impacted in an adult with complete permanent dentition with no other medical condition associated has never been reported in international literature until now.…”
Section: A S E R E P O R Tmentioning
confidence: 99%
“…[2][3][4][5] Many patients do not know about their impacted tooth and it is discovered during routine examinations. Therefore, it is very important to inform dental practitioners about this frequently occurring phenomenon in everyday clinical practice and to emphasize the importance of early detection and intervention to prevent possible harmful consequences 6 .…”
Section: Introductionmentioning
confidence: 99%
“…8,9 Tooth impaction ranges from 0.8-3.6% of the general population. 6,10 Some authors reported that third molar impaction rate is 16.7% to 68.6%. 11,12 Carter et al in a meta-analysis study found 24.4% worldwide third molar tooth impaction and they showed that impaction of third molars in mandible was greater than maxilla, but its prevalence was not significantly different between men or women.…”
Section: Introductionmentioning
confidence: 99%